Evaluation of teaching and learning in Anatomy at the St. Luke's College of Medicine William H. Quasha Memorial - Roxas, Marissa P.
This study aimed to evaluate the teaching and learning in anatomy at the St. Luke's College of Medicine. It obtained the perceptions of students concerning the components of the course, the performance of the department faculty and the adequacy of preparation of students for the clinical disciplines. The study made use of rating scales, focus group discussions, interviews and record reviews. The students' rating scale consisted of statements pertaining to the course and to the faculty's pedagogical skills. A rating scale on the teacher's classroom skills was also accomplished by the researcher. A series of focus group discussions were done to corroborate data. Members of clinical science departments were interviewed to obtain their views on how anatomy prepared students for the clinical subjects. Record review of laboratory equipment, library materials, course objectives, institutional objectives, lecture outlines and examination questions was done. The mean scores obtained from the course and faculty evaluation were determined. Results showed that the components of the course were viewed with uncertainty. However, the performance of the faculty particularly with respect to the choice and organization of subject matter and instructional skills were regarded favorably. The researcher's observation of the classroom performance of the faculty were likewise generally favorable Content analysis of the transcripts obtained from the focus group discussions and interviews revealed that anatomy was able to provide students with sufficient background for the study of clinical disciplines. Based on record reviews, these results were obtained: a) there is lack of congruence between course and college objectives, b) the school is able to provide students with sufficient laboratory and library resources, c) teachers organize their lectures based on a lecture outline or the format in textbooks and, d) many examination questions in gross anatomy lack content validity. It is recommended that modifications be made in these components of the course: course objectives, grading procedure, coverage of examinations, reports/assignments and laboratory sessions. It is also recommended that the faculty undergo further training on instructional strategies, test construction and evaluation techniques.